Potential to Enhance the Prescribing of Generic Drugs in Patients with Mental Health Problems in Austria; Implications for the Future - Godman, Brian; Burkhardt, Thomas; Bucsics, Anna; Piessnegger, Jutta; Schmitzer, Manuela; Barbui, Corrado; Bennie, Marion; Gustafsson, Lars L.; Raschi, Emanuel (Frontiers in Pharmacology, 2013)
Introduction: Scrutiny over pharmaceutical expenditure is increasing leading to multiple reforms. This includes Austria with measures to lower generic prices and enhance their utilisation. However the situation for newer antidepressants and atypical antipsychotic drugs (AAPs) is different to PPIs, statins and renin-angiotensin drugs with greater tailoring of therapy and no wish to switch products in stable patients. Authorities welcome generics though given high costs particularly of patented AAPs. Objective: Assess (a) changes in utilisation of venlafaxine versus other newer anti-depressants before and after availability of generics, (b) utilisation of generic versus originator venlafaxine, (c) price reductions of venlafaxine over time and influence on total expenditure, (d) utilisation of risperidone versus other AAPs, (e) suggest potential additional reforms that could be introduced if pertinent. Methodology: A quasi-experimental study design with a segmented time series and an observational study. Utilisation measured in defined daily doses (DDDs) and total expenditure per DDD and over time. Results: No appreciable changes in the utilization patterns of venlafaxine and risperidone after generics. The reduction in expenditure/ DDD for venlafaxine decreased overall expenditure on antidepressants by 5% by the end of the study versus just before generics despite a 37% increase in utilization. Expenditure will further decrease if there was reduced prescribing of duloxetine. Conclusion: Depression, schizophrenia and bipolar diseases are complex diseases. As a result, specific measures are needed to encourage prescribing of generic risperidone and venlafaxine when multiple choices are appropriate, and authorities cannot rely on a ´Hawthorne´ effect between classes to enhance use of generics first line. Measures may include prescribing restrictions for duloxetine. No specific measures planned for AAPs with more generics becoming available.